ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PADA KANTOR SATUAN POLISI PAMONG PRAJA DAN PEMADAM KEBAKARAN PROVINSI SULAWESI BARAT - Dallu, Abdul Syukur (LPPM Universitas Muhammadiyah Mamuju, 2019)
The organization is a collection of various human resources, each organization must continue to grow both quantitatively and qualitatively. Organizational growth not only maintains its existence but also in developing itself well in the framework of achieving organizational goals. One form of formal organization is the office organization, each organization needs to think of ways that can be done to develop employees in order to encourage employee performance in order to have productivity at work. The Office of the Civil Service Police Unit and the Fire Department of West Sulawesi Province is a government agency that requires good performance in carrying out its duties and functions to provide services to the community, for that the Office of the Civil Service Police Unit and the Fire Department of West Sulawesi Province in carrying out its role as a public servant requires good organizational climate for employees who have work motivation and discipline. Therefore, every activity carried out by employees can be driven by a force within the employee, this driving force is called motivation Discipline is an attitude to act in accordance with the provisions or norms that apply in the organizational environment Employee performance is important given the change in direction of government policy as desired by the spirit of reform to provide wider room for and greater participation for employees in the activities of the civil service police unit, where the government and its apparatus play a role as facilitators. This change in policy direction has implications for the professional capabilities of civil service police officers in responding to the challenges of the globalization era in the face of intense competition